Effect of cryogenic aging on nanophased fiber metal laminates and glass/epoxy composites. Issue 6 (12th October 2018) - Najafi, Moslem; Ansari, Reza; Darvizeh, Abolfazl
Abstract : In this study, the idea of using fiber metal laminate (FML) for cryogenic applications has been proposed. Considering the cryogenic durability of 5, 000 series of aluminum alloys, a novel FML based on the aluminum alloy 5083‐H111 was successfully developed. The changes in the mechanical properties of the mentioned FMLs, as well as traditional plain weave E‐glass/epoxy (GE) composites after exposure to cryogenic aging in LN2 at a temperature of −196°C for 336 h was evaluated. In addition, an effort was made on improvement of the cryogenic durability of both laminate types by adding montmorillonite nanoclay particles into the polymeric matrix. The principal findings were the maximum flexural load, flexural stiffness, and impact strength of GE composites were negatively affected by cryogenic aging and decreased by 26.82, 5.13, and 14.06%, respectively, while these values for the aged FMLs were only 18.65, 4.54, and 9.56%, respectively. It was also found that the nanoclay could effectively improve the mechanical properties of both laminate types in pristine and aged conditions. This study can provide a preliminary guideline for the initial design of the cryogenic tanks based on FMLs. POLYM. COMPOS., 40:2523–2533, 2019. © 2018 Society of Plastics Engineers